Analysis of Buying Interest: Price, Trust and Advertising (Study Literature Review) - Prihartono, Prihartono (Dinasti Publisher, 2021)
Literature Review Article Analysis of Buying Interest: Price, Trust and Advertising is a scientific article that aims to build a research hypothesis on the influence between variables that will be used in further research, within the scope of Marketing Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are that: 1) Price is related to Purchase Intention; 2) Trust is related to Buying Interest; and 3) Advertising related to Buying Interest. Apart from these 3 exogenous variables that affect the endogenous variable of Buying Interest, there are still many other factors including product quality, place and service quality variables.